In Vitro Regeneration Of Cinnamomum Tamala Nees From Cotyledonary Segments (Applied Biological Research, 2014)
Cinnamomum tamala Nees., a valuable spice-yielding plant of Himalaya, is vulnerable in its natural habitat due to its over-collection for spice and medicinal purpose. In the present study, a successful attempt was made  for in vitro shoot bud induction from cotyledons and plant regeneration.  The culturedcotyledons of 10-11wk after flowering induced meristematic  response within 4-5 wk of culture where ~43% explants responded  positivelyonMSmediumfortifiedwith 3% sucrose, polyvinyl pyrollidone  (100mgL-1) and 6 µM benzyl adenine wherein ~5-6 shoot buds developed cotyledon-1.Themicro-shoots/shoot buds,developedon initiation medium, were maintained on MS medium fortified with 3% sucrose and 3 µM  kinetin where shoot buds converted into plantlets and supported culture  proliferation. Shoots (4 cm long) with fully open leaves were rooted by  maintaining on MS medium enriched with 3 µM α-naphthalene acetic  acid where 5-6 roots developed per micro-shoot. The rooted plants were  transferred to potting mix and maintained in agro-shade ca75% shading  where ~65% transplants survived after two months of transfer.
Keywords: Cinnamomum tamala; cotyledonary segments; in vitro morphogenetic response; spice yielding plant